ASSERTIVE ILLOCUTIONARY ACTS STUDY OF BRITISH AND KOREAN IN KOREAN ENGLISHMAN YOUTUBE CHANNEL - Abdullah Muhammad, Akbar Ghifari (Jurnal Smart, 2021)
This study discusses the use of assertive illocutionary acts uttered by Beckham and Heung-Min in the videos of the Korean Englishman YouTube Channel. The study aims to discover the types and differences of assertive illocutionary acts used by the British, represented by Beckham, and Korean, represented by Heung-Min. This research is descriptive qualitative research as it is designed to get an in-depth understanding and analysis to describe the pattern of assertive illocutionary acts in British Culture and Korean Culture. British and Korean use assertive acts in their communication, but they use them differently. The differences occur because of cultural background differences. British tend to use assertive acts more directive. Korean mostly use assertive acts in the manner of thinking about other people's pride.